3(2x+5)=(3x+3)

Simple and best practice solution for 3(2x+5)=(3x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+5)=(3x+3) equation:


Simplifying
3(2x + 5) = (3x + 3)

Reorder the terms:
3(5 + 2x) = (3x + 3)
(5 * 3 + 2x * 3) = (3x + 3)
(15 + 6x) = (3x + 3)

Reorder the terms:
15 + 6x = (3 + 3x)

Remove parenthesis around (3 + 3x)
15 + 6x = 3 + 3x

Solving
15 + 6x = 3 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
15 + 6x + -3x = 3 + 3x + -3x

Combine like terms: 6x + -3x = 3x
15 + 3x = 3 + 3x + -3x

Combine like terms: 3x + -3x = 0
15 + 3x = 3 + 0
15 + 3x = 3

Add '-15' to each side of the equation.
15 + -15 + 3x = 3 + -15

Combine like terms: 15 + -15 = 0
0 + 3x = 3 + -15
3x = 3 + -15

Combine like terms: 3 + -15 = -12
3x = -12

Divide each side by '3'.
x = -4

Simplifying
x = -4

See similar equations:

| 5m+m-2m=20 | | 12n=7 | | 7p+2p+2p-p-2p=16 | | 16b-9b-b=18 | | y=-5t^2+20t+60 | | √2/2x-54=1/3 | | ln0.9/ln2= | | 17c+2c+2c-12c=9 | | 2t-2t+4t+t-3t=20 | | 7(2x+7)= | | 3p-2p+p= | | (a-2)/2=-1 | | 4(c-5)=12 | | 21=-3(1-2x)-6(x-5) | | 6r-r=20 | | -4x-5=-4x+13 | | 2(7x+1)= | | 17c-16c=7 | | 1x^3-12x+8=0 | | 2x^2+11x-63= | | 2x+3(2x-1)=25 | | 8.5y=-153 | | 0.88=5c+3c | | 17y=8y+81 | | 3x+-16=180 | | -8(-7p+1)=328 | | 800*5*x=250 | | 6x-9/7=10x | | 14-3w=4w | | 12x^2+15x+3= | | -2y=-4x-20 | | (Y+9)*(y+2)= |

Equations solver categories